2004
DOI: 10.1103/physrevlett.92.105702
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Lattice in theγαPhase Transition of Ce: A High-Pressure Neutron and X-Ray Diffraction Study

Abstract: The temperature and pressure dependence of the thermal displacements and lattice parameters were obtained across the γ → α phase transition of Ce using high-pressure, high-resolution neutron and synchrotron x-ray powder diffraction. The estimated vibrational entropy change per atom in the γ → α phase transition, ∆S γ−α vib ≈ (0.75±0.15)kB, is about half of the total entropy change. The bulk modulus follows a power-law pressure dependence which is well described using the framework of electron-phonon coupling. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
81
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 42 publications
15
81
0
Order By: Relevance
“…Since LDA+DMFT calculations do hint at a Van der Waals loop in the Ce free energy at about the right place, 42,43,44,46 the full story for Pr and Nd may await inclusion of the Hund's rules exchange for these multi-f electron cases, assumption of the correct structures for all phases (e.g., α-U), and possibly also adding lattice vibrational contributions. 56,57 Even so, this work suggests that the collapse transitions may not be the predominant story in the compressed trivalent rare earths, but rather consequences of an underlying and more robust evolution associated with 4f -electron delocalization. the latter are essentially on top of one another except for the charge case at the smallest volumes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since LDA+DMFT calculations do hint at a Van der Waals loop in the Ce free energy at about the right place, 42,43,44,46 the full story for Pr and Nd may await inclusion of the Hund's rules exchange for these multi-f electron cases, assumption of the correct structures for all phases (e.g., α-U), and possibly also adding lattice vibrational contributions. 56,57 Even so, this work suggests that the collapse transitions may not be the predominant story in the compressed trivalent rare earths, but rather consequences of an underlying and more robust evolution associated with 4f -electron delocalization. the latter are essentially on top of one another except for the charge case at the smallest volumes.…”
Section: Discussionmentioning
confidence: 99%
“…14 These temperature senstivities are also a reminder of the need to include lattice vibrational contributions, which may themselves further modify the nature of the collapse transitions. 56,57 …”
Section: Resultsmentioning
confidence: 99%
“…The phonon density of states (PDOS) of a Ce 0.9 Th 0.1 alloy at 150 K (γ-phase) and 140 K (α-phase) determined by inelastic neutron scattering (INS) (11) display very small differences across the transition, so that changes in the vibrational entropy, ΔS γ−α vib , have been suggested to be negligible. In contrast, high-pressure X-ray and neutron diffraction studies on polycrystalline Ce concluded that ΔS γ−α vib accounts for roughly half of the total entropy change (12). Further evidence for a large role of the vibrational energetics is provided by recent ultrasonic investigations (13,14) and a combined highpressure and high-temperature X-ray diffraction study (15).…”
mentioning
confidence: 94%
“…The divergence of the compressibility discussed above implies that the bulk modulus vanishes as |p − p ↑ | 1/2 and jumps discontinuously to a finite value for p > p ↑ . Remarkably, after this work was completed and a preliminary version of it was posted [29] this prediction was experimentally verified in Ce [30].…”
Section: Comparison With Experimentsmentioning
confidence: 99%